The impact of COVID-19 on urban informal workers in Maputo - Nilifer Anaç; Eva-Maria Egger; Sam Jones; Ricardo Santos; Alex Warren-Rodriguez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Informal self-employed traders in developing countries are vulnerable to shocks as they often lack access to social insurance or formal finance. This study investigates the impact of the COVID-19 pandemic on these urban traders in the capital of Mozambique, Maputo. Drawing on longitudinal phone survey data over six months, we find they experienced significant negative shocks to earnings, leading to a reduction in savings as well as worsening food security and assets. Individuals simultaneously affected by a municipal policy to remove informal traders from a central market were hit particularly hard as they lost their clients and market stalls. We simulate that a cash transfer equivalent to the government's proposed COVID-19 response would have significantly buffered these shocks. The findings point to the need for a more shock-responsive social protection system, easy access to liquidity and provision of market infrastructure for informal traders.
Keywords: I32; J46; O17; 330; COVID-19; informal; urban traders; Mozambique